2014
DOI: 10.1093/ejcts/ezu288
|View full text |Cite
|
Sign up to set email alerts
|

Skill acquisition process in vascular anastomosis procedures: a simulation-based study

Abstract: Although the most significant improvement was observed in Group I, all groups demonstrated improved skills with the simulation model. Therefore, it can be suggested that anastomosis training on tissue-based simulation models may be beneficial for the skill acquisition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The 16 studies were published between 2008 and 2017 in peer reviewed journals [12,14,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, no study was published in medical education periodicals.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 16 studies were published between 2008 and 2017 in peer reviewed journals [12,14,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, no study was published in medical education periodicals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies were in English. Eleven studies (68.7%) were from North America training programs [12, 14, 45-47, 50, 51, 53-56], three (18.7%) were from Asia [48,49,57]. and one each (6.2%) was from Europe [44] and South America [52].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study, with a short duration and low intensity of training, also suggests that training can improve the surgical skills of physicians. Another study has shown that training-even low-intensity training-is beneficial for the skill acquisition process ( 21 ). A recent survey of Chinese physicians reported that the number of doctors aged 36–45 years accounted for 32.53% of the total number of doctors.…”
Section: Discussionmentioning
confidence: 99%